PANCREATIC HORMONES AND THEIR FUNCTIONS - Yuldosheva Roila Jumaevna (Journals Park Publishing, 2022)
The pancreas plays a key role in regulating the digestion of macronutrients and, consequently, metabolism/energy homeostasis by secreting various digestive enzymes and pancreatic hormones. It is located behind the stomach in the upper left part of the abdominal cavity and is divided into a head, body and tail. Most of this secretory organ consists of acinar or exocrine cells that secrete pancreatic juice containing digestive enzymes such as amylase, pancreatic lipase and trypsinogen into the ducts, that is, into the main pancreatic and auxiliary pancreatic ducts.
Keywords: metabolism; insulin; endocrine system